The Cancer Genome Atlas Comprehensive Molecular Characterization of Renal Cell Carcinoma. - Ricketts, Christopher J.; De Cubas, Aguirre A.; Fan, Huihui; Smith, Christof C.; Lang, Martin; Reznik, Ed; Bowlby, Reanne; Gibb, Ewan A.; Akbani, Rehan; Beroukhim, Rameen; Bottaro, Donald P.; Choueiri, Toni K.; et al. (Cell Reports, 2018)
Renal cell carcinoma (RCC) is not a single disease, but several histologically defined cancers with different genetic drivers, clinical courses, and therapeutic responses. The current study evaluated 843 RCC from the three major histologic subtypes, including 488 clear cell RCC, 274 papillary RCC, and 81 chromophobe RCC. Comprehensive genomic and phenotypic analysis of the RCC subtypes reveals distinctive features of each subtype that provide the foundation for the development of subtype-specific therapeutic and management strategies for patients affected with these cancers. Somatic alteration of BAP1, PBRM1, and PTEN and altered metabolic pathways correlated with subtype-specific decreased survival, while CDKN2A alteration, increased DNA hypermethylation, and increases in the immune-related Th2 gene expression signature correlated with decreased survival within all major histologic subtypes. CIMP-RCC demonstrated an increased immune signature, and a uniform and distinct metabolic expression pattern identified a subset of metabolically divergent (MD) ChRCC that associated with extremely poor survival.
EVALuna2:34860